2015
DOI: 10.1503/cjs.030313
|View full text |Cite
|
Sign up to set email alerts
|

Tension plate for treatment of olecranon fractures: new surgical technique and case series study

Abstract: Background: Our aim was to determine the effectiveness of a new surgical technique for olecranon fractures using a tension plate (TP) designed by the operating surgeon. Methods:We included patients with olecranon fractures treated between September 2010 and August 2013 in our study. Treatment involved a new implant and operative technique, which combined the most favourable characteristics of 2 frequently used methods, tension band wiring and plate osteosynthesis, while eliminating their shortcomings. The new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Compared with TBW, PF possesses the advantage of an increased stability [31] and is related to lower rates of hardware prominence [34]. Luksic et al [25] reported that in the treatment of comminuted olecranon fractures a new technical tension plate combined with two Kirschner wires could provide adequate stability for early postoperative functional recovery, producing good clinical outcomes and increasing the fracture union rate [25]. However, hardware-related symptoms have been a common complication, with a rate of approximately 56 to 76.2%, leading to a secondary operation for removal [1,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with TBW, PF possesses the advantage of an increased stability [31] and is related to lower rates of hardware prominence [34]. Luksic et al [25] reported that in the treatment of comminuted olecranon fractures a new technical tension plate combined with two Kirschner wires could provide adequate stability for early postoperative functional recovery, producing good clinical outcomes and increasing the fracture union rate [25]. However, hardware-related symptoms have been a common complication, with a rate of approximately 56 to 76.2%, leading to a secondary operation for removal [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…The Mayo Elbow Performance (MEP) score was also used as a comprehensive assessment considering the following four factors: pain, ulnohumeral motion, stability, and the ability to perform five functional tasks [ 24 ]. According to the previous report [ 25 ], the functional range of movement in the operated elbow was flexion ≥ 128°, extension ≥ 116°, and pronation and supination ≥ 72°; when any one of the elbow joints does not meet these 4 criteria, we considered it a loss of the functional range of motion. All the clinical assessments used in this study were performed by independent observers, and the results were independently interpreted by two authors.…”
Section: Methodsmentioning
confidence: 99%